Post-COVID-19 bifacial weakness and paraesthesia: a case report (Swiss Medical Weekly, 2021)
OBJECTIVES: We present a patient with bifacial weakness and paraesthesia subtype of Guillain-Barré syndrome (GBS), which occurred 1 month after a SARS-CoV-2 infection. While GBS as complication of SARS-CoV-2 infection has been described many times, only a few cases of post-COVID-19 bifacial weakness and paraesthesia are known to date.RESULTS: A 59-year-old man presented with thoracoradicular pain, paraesthesias of hands and feet, as well as progressive bilateral facial palsy. Neurological examination revealed a hyporeflexia of his lower limbs and hypoaesthesia of his hands and feet. Clinical and electrophysiological findings as well as CSF analysis were consistent with bifacial weakness and paraesthesia. The patient’s condition improved promptly after 5 days of intravenous immunoglobulin therapy.DISCUSSION: We suspect bifacial weakness and paraesthesia to be a possible post-infectious complication of COVID-19. Hence, it is a differential diagnosis of facial nerve palsy in association with SARS-CoV-2 infection. Considering the rarity of GBS and bifacial weakness and paraesthesia, it appears unlikely that bigger trials elucidating the causal relation between them and SARS-CoV-2 infection will be available in the future.